prove

Asked by  | 24th Apr, 2008, 06:56: PM

Expert Answer:

cosecA - cosec2 A =  cot4A + cot2

RHS

(cosec2A)2 - cosec2A

= cosec2A ( cosec2 -- 1)

=(1 + cot2A) cot2A

cot2A + cot4A = LHS

 

tanA + tan B /cot A + cot B =tan A tan B

RHS

tan A + tan B / cot A + cot B

=tan A + tan B /   1/ tan A + 1/ tan B

=tan A + tan B  /  tan A +  tan B /tan A  tan B

=   ( tan A + tan B ) ( tan A Tan B) /tan A + tan B

tan A tan B = LHS

 

 

Answered by  | 24th Apr, 2008, 10:13: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.